2006 IEEE/ACM International Symposium on Mixed and Augmented Reality 2006
DOI: 10.1109/ismar.2006.297788
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of visual capabilities using augmented reality displays

Abstract: In order to be able to perceive and recognize objects or surface properties of objects, one must be able to resolve the features. These perceptual tasks can be difficult for both graphical representations and real objects in augmented reality (AR) displays. This paper presents the results of objective measurements and two user studies. The first evaluation explores visual acuity and contrast sensitivity; the second explores color perception. Both experiments test users' capabilities with their natural vision a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…For OST devices, particular attention should be paid when using color codes, because colors are differently saturated depending on backgrounds, even if still perceived as their original hues as revealed by Gabbard et al [4]. Furthermore Livingston's experiments on HWDs [28], [29], especially OST ones, showed that dark color tended to disappear perceptually with light backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…For OST devices, particular attention should be paid when using color codes, because colors are differently saturated depending on backgrounds, even if still perceived as their original hues as revealed by Gabbard et al [4]. Furthermore Livingston's experiments on HWDs [28], [29], especially OST ones, showed that dark color tended to disappear perceptually with light backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…All users scored 20/30 looking at a graphical chart. This test was extended to a 2D contrast sensitivity measure using a sine-wave chart [20]. The Glasstron notably reduced the contrast sensitivity of the user compared to his or her normal vision, though it should be noted that the contrast levels in this experiment were well below the standard for optometric exams.…”
Section: Visual Acuitymentioning
confidence: 90%
“…One can also quantify the perception of color through head-worn AR displays using a color naming task. The reduction of contrast in the Glasstron noted for the visual acuity and contrast sensitivity test appeared to also cause some color confusion near the white point of the CIE 1931 color space, especially when looking at real-world objects through the see-through optics [20]. Color samples near the boundaries of named regions were inconsistently labeled, with lighter colors progressively less consistent in their names.…”
Section: Color Perceptionmentioning
confidence: 93%
“…In previous experiments [6], we tested contrast sensitivity and color naming. The Sony Glasstron notably reduced the contrast sensitivity of the user compared to his or her normal vision, though it should be noted that the contrast levels in this experiment were well below the standard for optometric exams.…”
Section: Visual Perception In Head-worn Displaysmentioning
confidence: 99%